Hadith #3625 - Sahih al-Bukhari - Abu Hamzah Anas ibn Malik (Sahih al-Bukhari)
(A man from the Ansar) The Ansar said, “Every nation has followers and (O Prophet) we have followed you, so invoke Allah to let our followers be considered from us (as Ansar like ourselves).” So the Prophet (ﷺ) said, “O Allah! Let their followers be considered as Ansar like themselves.”
Grade: Sahih